Real Rigidity, Nominal Rigidity, and the Social Value of Information - Angeletos, George-Marios; Iovino, Luigi; La'O, Jennifer (American Economic Review, 2016)
Does welfare improve when firms are better informed about the state of the economy and can thus better coordinate their production and pricing decisions? We address this question in an elementary business-cycle model that highlights how the dispersion of information can impede both kinds of decisions and, in this sense, be the source of both real and nominal rigidity. Within this context we develop a taxonomy for how the social value of information depends on the two rigidities, on the sources of the business cycle, and on the conduct of monetary policy. (JEL D21, D82, D83, E32, E52)